DESAIN SISTEM INFORMASI AKUNTANSI BERDASARKAN SAK 45 UNTUK PENGELOLAAN KEUANGAN PADA YAYASAN KARMEL MALANG - Galuh Budi Astuti; Lis Lestari Sukartiningsih; F.X. Agung Jampur Prakoso (Akubis : Jurnal Akuntansi dan Bisnis, 2020)
This research is intended to prepare accounting informationsystem in Yayasan Karmel to comply with SAK 45 standard sothat the information presented is appropriate and can be usedin decision making. This research is case study which gives adetailed description of the application of SAK 45 in thefinancial report of Karmel Foundation for further analysis sothat it can be found conclusions and handling problems with.The output of this research is the design of systems anddatabases, research reports and publications of researchresults in unaccredited national journals. The scope ofresearch in the field of designing accounting information inaccordance with SAK 45 so that the information presented inthe financial statements of the Karmel Foundation is moreaccurate for decision making. From the analysis of theorganizational structure for the preparation of functions, flowand related procedures in the Karmel Foundation financialstatements, system analysis, documents and recordingprocedures to understand internal controls in KarmalFoundation and analysis of periodic financial statements thathave been made then Karmel Foundation requires systemDesign the appropriate database. Design SIA with contextdiagram level 0, level I-4 and level I-5 with the user that is thecash, accounting and head of finance.